The Teachers’ perception of Continuous Professional Development “CPD” effectiveness in Higher Education in Kurdistan: CPD - Mahdi Azeez Qader (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2019)
Abstract This research project is a case study conducted to investigate